Shumkova's Kazan Women's Gymnasium with Professional Division: Ways of democratization of female education in pre-revolutionary Russia - S.A. Ezhova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper considers the private educational institution evolution in the context of female education democratization in pre-revolutionary Russia. The role and importance of schools in the development of female professional education in Kazan during the second half of the 19th – early 20th centuries have been shown; the features of educational, social, and educational policy of schools have been revealed. Based on a wide range of sources, the practical significance of the long-term fruitful cooperation between L.P. Shumkova, the founder of the gymnasium, and P.I. Alexandrov, a philanthropist of the school, has been studied. Thanks to this interaction, a small primary school developed over time into a kind of educational complex, which united several independent departments: gymnasium, courses for the training of needlework teachers, evening general education courses for adults, a professional department, and a mixed primary school. The paper discusses the main stages of school development throughout the entire period of its existence. Representatives of socially disadvantaged groups of the population prevailed among the schoolgirls, who, in addition to acquiring professional competencies, were attracted to the school by the system of benefits and allowances. Having been a unique educational institution that combined a general education gymnasium course with high-quality vocational training, the gymnasium had a well-deserved reputation in the Kazan Governorate and other regions. The historical and pedagogical study of the experience of the gymnasium makes it possible to enrich modern science with the knowledge of the ways of democratization and the mechanisms of modernization of the women's school in Russia.